Memahami Logika Berpikir Sebagai Landasan Membangun Argumentasi Yang Kuat - Walde Mesah; Ferdi Eka Darma; Mozes Lawalata (Sekolah Tinggi Pastoral Kateketik Santo Fransiskus Assisi, 2024)
In a world full of arguments and opinions, the ability to understand the logic of thinking is a strong foundation for creating persuasive arguments. Logical thinking involves using meaningful rules and principles to form reasonable arguments based on available information. The basic principles of logic, such as the identity principle, the contradiction principle, and the refutation principle, are the basis for consistent and correct reasoning. Understanding and avoiding logical fallacies is also important for developing critical thinking and strong reasoning. In argumentation, logic plays an important role in creating strong and convincing arguments. By using strong evidence, assessing relevance, and thinking critically, you can avoid reasoning errors and create stronger arguments. In argumentation and debate, arguments that are based on logic and strong evidence are generally accepted and taken more seriously by opponents and listeners. Therefore, it is important to develop a good understanding of logical thinking and use it effectively to create strong and convincing arguments. Understanding the basic principles of logic will help you identify weaknesses in arguments, evaluate evidence critically, and create more effective arguments. Thus, logical thinking becomes an important basis for creating strong and convincing arguments.